For love and money: the need to rethink benefits in HIV cure studies - Largent, Emily (Journal of medical ethics, 2017)
HIV cure research holds great potential to eradicate HIV, but the benefit to early trial participants is likely to be small. Moreover, participation carries unknown and possibly significant risks to research participants. This is the risk:benefit ratio challenge of HIV cure research. Although it may be consensual and rational for individuals to participate in HIV cure research that requires a degree of self-sacrifice, I argue that altruistic research participants can be exploited when the benefits to them are unfair. Transactions of this kind should not be prohibited, as that would be unacceptably paternalistic and thwart socially valuable research. Nevertheless, we should not simply accept these transactions but must work to reduce or eliminate exploitation by enhancing the benefits so that research participants are better off by their own lights. Offering payment in HIV cure research is the optimal way to enhance benefits to research participants and to make the risk:benefit ratio more favourable. I argue for a payment-as-benefit model against the standard view, assumed in ethics and policy, that offers of payment are not legitimate benefits.